Pearls of Glaucoma Management - Giaconi, JoAnn A.; Law, Simon K.; Coleman, Anne L.; Caprioli, Joseph; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This concise and comprehensive guide is written by international experts of the field who are familiar with the world$1 (Bs literature. Based on the world$1 (Bs literature and their own experience, authors state and explain how they prefer to manage patients and problems clinically. Each chapter author gives the reader numerous clear and specific tips and pearls for the diagnosis and management of Glaucoma. The reader-friendly structure of this lavishly illustrated 4-colour book ensures that the necessary information is quickly found and remembered. This book ensures a pleasant learning experience on Glaucoma management with the goal of an improved treatment outcome.s
Optic Nerve: The Glaucomatous Optic Nerve -- Optic Nerve: Clinical Examination -- Optic Nerve: Heidelberg Retinal Tomography -- Optic Nerve: Scanning Laser Polarimetry -- Optic Nerve: Optical Coherence Tomography -- Optic Nerve: Comparison of Technologies -- Optic Nerve: Atypical Nerves and Nerve Findings -- IOP: The Importance of Intraocular Pressure -- IOP: Instruments to Measure IOP -- IOP: Central Corneal Thickness -- IOP: Corneal Hysteresis -- IOP: Target Pressures -- IOP: Fluctuation -- Gonioscopy: Why Do Indentation? -- Visual Fields: Visual Field Test Strategies -- Visual Fields: Fluctuation and Progression -- Visual Fields: Field Interpretation -- Other Tests in Glaucoma: Genetic Testing -- Other Testing in Glaucoma: Optic Nerve Blood Flow I -- Other Tests in Glaucoma: Optic Nerve Blood Flow II -- Other Tests in Glaucoma: Multifocal Visual Evoked Potential -- Risk Factors -- Risk Factors: The Risk Calculator -- Medical Treatment: First Line Agents and Monotherapy -- Medical Treatment: The Pregnant and Nursing Woman -- Medical Treatment: Carbonic Anhydrase Inhibitors -- Medical Treatment: Osmotic Agents -- Medical Treatment: Neuroprotection -- Medical Treatment: Treated vs. Untreated Glaucoma and Ocular Hypertension -- Medical Treatment: Adherence and Persistence -- Medical Treatment: Alternative Medicine and Glaucoma -- Procedural Treatments: Laser Trabeculoplasty -- Procedural Treatments: Endoscopic Cyclophotocoagulation -- Procedural Treatments: Transcleral Cyclophotocoagulation -- Procedural Treatments: Trabeculectomy -- Procedural Treatments: Perioperative Medication -- Procedural Treatments: Bleb Needling -- Procedural Treatments: Glaucoma Drainage Devices -- Procedural Treatments: New Surgical Options -- Procedural Treatments: Ex-PRESS Mini Glaucoma Shunt -- Procedural Treatments: Phacotrabeculectomy -- Procedural Treatments: Surgery in End-Stage Glaucoma -- Glaucomas: Managing Normal-Tension Glaucoma -- Glaucomas: Pseudoexfoliation Glaucoma -- Glaucomas: Pigment Dispersion Glaucoma and Angle Recession Glaucoma -- Glaucomas: Sturge Weber Syndrome -- Glaucomas: Glaucoma and the Cornea -- Glaucomas: Uveitic Glaucoma -- Glaucomas: Neovascular Glaucoma -- Pediatric Glaucoma: IOP, Axial Length, and Surgery Indications -- Pediatric Glaucoma: Glaucoma Medications and Steroids -- Pediatric Glaucoma: Angle Surgery and Glaucoma Drainage Devices -- Pediatric Glaucoma: Trabeculectomy and Glaucoma Drainage Devices -- Angle-Closure Glaucoma: Risk Factors -- Angle-Closure Glaucoma: Iridotomy -- Angle-Closure Glaucoma: Imaging -- Angle-Closure Glaucoma: Medical Therapy -- Angle-Closure Glaucoma: Surgical Management of Acute Angle-Closure Glaucoma -- Complications: Hypotony -- Complications: Bleb Leaks -- Complications: Blebitis.
Keywords: Medicine; Ophthalmology; Optical materials; Medicine & Public Health; Ophthalmology; Optical and Electronic Materials